A New Evidence for Sophocles’ Tragedy of “Phaedra” - Zhizhina-Hefter, Vera B. (Actual Problems of Theory and History of Art, 2017)
In the E. D. Trendall & T. B. L. Webster’s collection of illustrations to Greek drama an image on the lid of a red-figured Apulian pyxis (4th century BC) presents a human figure, dressed as a woman, leaning overa sword stuck in the ground, her face full of sorrow. Another figure — a bearded man by her side — also holds a sheathed sword and applies to the woman with a gesture of admonition. These two were identified by Websteras Phaedra and Theseus respectively; he also supposed the whole scene to be an illustration to an episode from Seneca’s Phaedra (vv. 704–897). According to Webster, a common source could explain this similarity. As such asource he chooses Euripides’ tragedy Hippolytos Calyptomenos that has not survived to the present day. During centuries the only assistance in reconstruction of the plays based on the myth about Hippolytus and Phaedra (i.e. Sophocles’ Phaedra and Hippolytos Calyptomenos) were few mythographers’ testimonies and several surviving fragments of the plays themselves (frr. 677–693 Radt and frr. 428–447 Kannicht resp.). Still, in view of newly discovered and published papyri all the previous reconstructions appeared to be inappropriate. In the first Euripides’ Hippolytos there must have been an episode when Phaedra after being rejected sends a slandering letter to Theseus. This peculiar detail in the first version of Hippolytos is proved by the papyrus fragments.Therefore the Hippolytos Calyptomenos contained no episode of oral slandering. However the vase-painter of the 4th century BC and Seneca in the 1st century AD should have had common source for their works, and it seems likely that Sophocles’ Phaedra should be recognized as the only candidate for this role.